NATO 1948 : the birth of the transatlantic Alliance - Kaplan, Lawrence S. (Rowman & Littlefield, 2007)
This compelling history brings to life the watershed year of 1948, when the United States reversed its long-standing position of political and military isolation from Europe and agreed to an 'entangling alliance' with ten European nations. The historic North Atlantic Treaty was signed on April 4, 1949, but the often-contentious negotiations stretched throughout the preceding year. Lawrence S. Kaplan, the leading historian of NATO, traces the tortuous and dramatic process, which struggled to reconcile the conflicting concerns on the part of the future partners. He brings to life the colorful di.